Desain Penyelesaian Kredit Macet Pembiayaan Murâbahah BMT Bina Ummat Sejahtera Melalui Pendekatan Socio Legal Research. - Supriyadi, Supriyadi (al-'adalah, 2016)
Abstract: Bad Debt Settlement Design in Murâbahah Financing of BMT Bina Ummah Sejahtera with Approace of Socio Legal Research. This article evaluates the operations of Islamic financing in BMT Bina Ummah Sejahtera, particularly in dealing with bad credit problems. This study concludes that the credit crunch occurring in the BMT is caused by both internal and external factors. The Internal factors relates to a number of falacies, such as: (1) The inaccuracy of employees in providing financing by not doing BI Checking to know the track record of a prospective customer. (2) Weak supervision of the management; (3) Not all financing agreement follow the procedure applicable by law; (4) contract agreements offered were not in favor of the BMT. External factors include; (1) Member bad character, (2) member experience bad luck such as bankruptcy or Household problems. Hence, it is advisable that oversight and enforcement are strictly performed by the government upon the Islamic financial institutions, assuring them to apply existing regulation. By doing so the Islamic finance institution can be expected to be a solution for the national economic development.Abstrak: Desain Penyelesaian Kredit Macet Pembiayaan Murâbahah BMT Bina Ummat Sejahtera Melalui Pendekatan Socio Legal Research. Artikel ini mengevaluasi operasional pembiayaan syariah di BMT Bina Ummat Sejahtera khususnya dalam menangani masalah kredit macet. Hasil penelitian menyimpulkan bahwa kredit macet yang terjadi di BMT tersebut disebabkan oleh faktor internal dan faktor eksternal. Faktor internal berkait dengan: ketidaktelitian dari karyawan dalam memberikan pembiayaan, tidak dilakukannya BI Checking untuk mengetahui rekam jejak calon nasabah. Lemahnya pengawasan dari pimpinan, tidak semua perjanjian pembiayaan mengikuti prosedur hukum yang berlaku, akad perjanjian yang ditawarkan tidak menguntungkan pihak BMT. Sedangkan faktor eksternal meliputi: iktikad buruk anggota, anggota mengalami musibah misalnya pailit atau mengalami problem rumah tangga. Untuk itu, disarankan adanya pengawasan dan penertiban secara ketat oleh pemerintah terhadap lembaga keuangan syariah agar mentati peraturan perundangan yang berlaku sehingga pembiayaan syariah dapat menjadi solusi dalam pembangunan ekonomi nasional.